2009
DOI: 10.4238/vol8-2kerr029
|View full text |Cite
|
Sign up to set email alerts
|

Pollen foraging in colonies of Melipona bicolor (Apidae, Meliponini): effects of season, colony size and queen number

Abstract: AbStrAct. We evaluated the ratio between the number of pollen foragers and the total number of bees entering colonies of Melipona bicolor, a facultative polygynous species of stingless bees. The variables considered in our analysis were: seasonality, colony size and the number of physogastric queens in each colony. The pollen forager ratios varied significantly between seasons; the ratio was higher in winter than in summer. However, colony size and number of queens per colony had no significant effect. We conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These results are validated by the observations of Borges and Blochtein (2005), who observed that temperatures above 13.7°C during the autumn-winter were instrumental in initiating the flight activity of M. obscurior. Another possibility for the low richness of pollen types is a decrease in the external activities of the M. obscurior colonies related to a discontinuation (diapause) in reproductive activity resulting from low temperatures (Hilário and Imperatriz-Fonseca 2009). Facultative reproductive diapause was observed for the same species in this geographic region by Borges and Blochtein (2006).…”
Section: Discussionmentioning
confidence: 71%
“…These results are validated by the observations of Borges and Blochtein (2005), who observed that temperatures above 13.7°C during the autumn-winter were instrumental in initiating the flight activity of M. obscurior. Another possibility for the low richness of pollen types is a decrease in the external activities of the M. obscurior colonies related to a discontinuation (diapause) in reproductive activity resulting from low temperatures (Hilário and Imperatriz-Fonseca 2009). Facultative reproductive diapause was observed for the same species in this geographic region by Borges and Blochtein (2006).…”
Section: Discussionmentioning
confidence: 71%
“…According to this study, both the availability and localization of floral resources affect the choice of the pollen sources in this species. In M. bicolor, pollen forager ratios varied significantly between seasons and this variation was related to both the production of reproductives and the number of individuals in the colonies (Hilário & Imperatriz-Fonseca, 2009). Quezada-Euán et al (2011) also reported that the worker's body size of Nannotrigona perilampoides may change according to the protein and sugar concentration in larval food.…”
Section: Discussionmentioning
confidence: 97%
“…The influence of weather on foraging activities has been studied in several eusocial bee species [14][15][16][17][18][19][20][21][22][23][24][25]. These studies report that weather conditions, light intensity, humidity, food availability, competition, colony state, and physiological conditions of individuals are important factors that influence the foraging activities of Melipona species.…”
Section: Introductionmentioning
confidence: 99%